2017
DOI: 10.1186/s13068-017-0834-9
|View full text |Cite
|
Sign up to set email alerts
|

Sweet sorghum as biofuel feedstock: recent advances and available resources

Abstract: Sweet sorghum is a promising target for biofuel production. It is a C4 crop with low input requirements and accumulates high levels of sugars in its stalks. However, large-scale planting on marginal lands would require improved varieties with optimized biofuel-related traits and tolerance to biotic and abiotic stresses. Considering this, many studies have been carried out to generate genetic and genomic resources for sweet sorghum. In this review, we discuss various attributes of sweet sorghum that make it an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
119
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(141 citation statements)
references
References 156 publications
1
119
0
4
Order By: Relevance
“…These results have implications in the context of bioenergy sorghum breeding (Mathur et al, 2017;de Oliveira et al, 2018;Regassa & Wortmann, 2014). It also showed that the effect of water deficit and rewatering on stem biomass production and composition is genotype and trait dependent.…”
Section: Insight For Biomass Sorghum Improvement and Managementmentioning
confidence: 81%
See 1 more Smart Citation
“…These results have implications in the context of bioenergy sorghum breeding (Mathur et al, 2017;de Oliveira et al, 2018;Regassa & Wortmann, 2014). It also showed that the effect of water deficit and rewatering on stem biomass production and composition is genotype and trait dependent.…”
Section: Insight For Biomass Sorghum Improvement and Managementmentioning
confidence: 81%
“…The response to water availability of traits related to stem growth and biochemistry was poorly correlated as well as the drought sensitivity and recovery capacity for a given trait. These results have implications in the context of bioenergy sorghum breeding (Mathur et al, 2017;de Oliveira et al, 2018;Regassa & Wortmann, 2014). First, stem biomass production and composition have to be considered jointly to develop new varieties relevant for the different value chains.…”
Section: Insight For Biomass Sorghum Improvement and Managementmentioning
confidence: 99%
“…Sorghum is the fifth most important cereal crop in the world. Grain sorghum varieties provide an important staple food and feed supply, while sweet and forage sorghum varieties are cultivated for biofuel and fodder markets, respectively (Calvino and Messing, 2012;Mathur et al, 2017;Smith and Frederiksen, 2000). Compared to sugarcane, sorghum is adapted to both tropical and temperate growing regions due to its higher water use efficiency and the ability to enter growth arrest when facing drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Variety of Super 2 (V3) has the highest stem that is 301.28 cm (Table 2) and followed by a high number of total biomass (Table 3), as stated at [20] that plant height is directly proportional to biomass. From 4 different varieties, variety of Super 2 (V3) has the highest result of the dry weight of stem, dry weight of leaf, dry weight of panicle and total of biomass.…”
Section: Resultsmentioning
confidence: 88%